2016
DOI: 10.1158/0008-5472.can-15-3284
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome Analysis of Triple-Negative Breast Cancer Reveals an Integrated mRNA-lncRNA Signature with Predictive and Prognostic Value

Abstract: While recognized as a generally aggressive disease, triplenegative breast cancer (TNBC) is highly diverse in different patients with variable outcomes. In this prospective observational study, we aimed to develop an RNA signature of TNBC patients to improve risk stratification and optimize the choice of adjuvant therapy. Transcriptome microarrays for 33 paired TNBC and adjacent normal breast tissue revealed tumor-specific mRNAs and long noncoding RNAs (lncRNA) that were associated with recurrence-free survival… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
170
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 169 publications
(176 citation statements)
references
References 46 publications
2
170
0
1
Order By: Relevance
“…[10][11][12] Previous studies have showed that LINC00319 is involved in the occurrence and development of lung cancer. [10][11][12] Previous studies have showed that LINC00319 is involved in the occurrence and development of lung cancer.…”
Section: Discussionmentioning
confidence: 99%
“…[10][11][12] Previous studies have showed that LINC00319 is involved in the occurrence and development of lung cancer. [10][11][12] Previous studies have showed that LINC00319 is involved in the occurrence and development of lung cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Triple-negative breast cancer account for one fifth of all breast cancers. Jiang et al reported lncRNA HIF1A-AS2 and AK124454 contributed to paclitaxel resistance in triple-negative breast cancer through transcriptome analysis [66]. …”
Section: Long Non-coding Rna In Cancer Cell Drug Resistancementioning
confidence: 99%
“…However, this signature was limited by the number of probes covering lncRNA loci (195 lncRNAs were differentially expressed between normal and tumor) on the Affymetrix Human Transcriptome Array 2.0 implying that this signature can be improved if developed with RNAseq data. Functionally, they confirmed that the two lncRNAs in the signature—HIF1A-AS2 and AK124454—promote proliferation, invasion, and paclitaxel resistance [89]. …”
Section: Global Analyses Reveal Widespread Dysregulation Of Lncrmentioning
confidence: 89%
“…Jiang et al performed a prospective observational study that demonstrated an integrated mRNA-lncRNA signature had better prognostic value to predict recurrence-free survival and pathologic complete remission after taxane-based neoadjuvant chemotherapy than clinicopathologic parameters in a cohort of 275 TNBC patients [89]. However, this signature was limited by the number of probes covering lncRNA loci (195 lncRNAs were differentially expressed between normal and tumor) on the Affymetrix Human Transcriptome Array 2.0 implying that this signature can be improved if developed with RNAseq data.…”
Section: Global Analyses Reveal Widespread Dysregulation Of Lncrmentioning
confidence: 99%